2017
DOI: 10.1080/13102818.2017.1389302
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Saccharomyces cerevisiae using polyethyleneimine grafted collagen fibre as support and investigations of its fermentation performance

Abstract: In the present investigation, an collagen fibre (CF), abundant natural biomass, was successfully grafted by polyethyleneimine (PEI). The resultant PEI grafted collagen fibre (CF-PEI) was employed as biocompatible and high cell loading support matrix for the immobilization of Saccharomyces cerevisiae cells. The as-prepared CF-PEI immobilized cells (CF-PEI-cell) exhibited high activity and stability for both batch and continuous fermentation. In batch fermentation, CF-PEI-cells showed enhanced stability as compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
1
14
1
Order By: Relevance
“…When comparing the systems of Najafpour et al 6 and Zhu et al 9 with that of Seo et al, 10 it is observed that equivalent productivity and efficiency are obtained at the microscale. Seo et al 10 obtained productivity of 5.75 g L −1 h −1 and efficiency of 75%.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…When comparing the systems of Najafpour et al 6 and Zhu et al 9 with that of Seo et al, 10 it is observed that equivalent productivity and efficiency are obtained at the microscale. Seo et al 10 obtained productivity of 5.75 g L −1 h −1 and efficiency of 75%.…”
Section: Resultsmentioning
confidence: 92%
“…In the macrosystems of Najafpour et al 6 and Zhu et al, 9 despite high efficiency of 88% and 89%, ethanol productivity was 3.8 and 7.2 g L −1 h −1 , respectively. This is due to the residence time of approximately 6 h used by both authors.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Since the 1970s, various methods for microbial immobilisation have been proposed ( 12,13 ) , and several bioprocesses have been established using immobilised cell technology, such as vinegar production ( 2 ) and wastewater treatment ( 13 ) . In general, there are four recognised methods for whole cell immobilisation, based on the type of interaction between cells and the support.…”
Section: Methods Of Immobilisationmentioning
confidence: 99%
“…The materials used for cell entrapment include polysaccharide gels, such as alginates, κ-carrageenan and chitosan (28)(29)(30)(31)(32)(33). In addition, cellulosic materials, ceramic-like materials and gelatines have also been used (12,32,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). The porosity of the material is the most important variable that determines the success or failure of the support.…”
Section: Cell Entrapmentmentioning
confidence: 99%